Blockchain and credibility function based chain storage method of electronic encrypted information - Ting ZHOU (Dianxin kexue)
To optimize the proportion of encrypted information storage space in the blockchain and improve the speed of online storage, a design method for electronic encrypted information online storage based on blockchain and credibility function was proposed.An information encryption classification model based on blockchain and credibility function was established, and a traceability voucher judgment function was obtained.Proxy re-encryption was performed on electronic information.The storage capacity of the cluster was calculated, and encrypted ciphertext was used to directly match the access structure tree.Subject credibility and object credibility were distinguished, electronic encrypted information was classified based on the credibility function, and an electronic encrypted information uplink storage method was designed.The experimental results show that after applying the proposed method, when the number of files is between 1 000 and 10 000, the data storage speed is the fastest, and the storage space proportion and storage speed are greatly optimized.